Pengaruh Padat Tebar terhadap Kelangsungan Hidup dan Pertumbuhan Ikan Lele Dumbo (Clarias gariepinus) dalam Sistem Budikdamber - Ngefak, Putra Marco; Salosso, Yuliana; Djonu, Asriati (Nusa Cendana University, 2025)
Budikdamber has emerged as a practical food-production strategy for urban areas with limited land resources, making it necessary to examine how stocking density influences the growth performance and survival of African catfish (Clarias gariepinus) cultured under this system. This study was conducted from June to August 2024 at the Aquaculture Field Laboratory, Universitas Nusa Cendana. The experiment employed a completely randomized design (CRD) consisting of three treatments with three replicates each: A (20 fish per container), B (30 fish per container), and C (40 fish per container). The evaluated parameters included survival rate, weight gain, and absolute length growth. The statistical analysis indicated that stocking density had a significant effect on survival (P<0.05), with treatment A achieving the highest survival rate of 100%. In contrast, no significant differences were detected for weight and length growth among treatments (P>0,05), although lower densities tended to support slightly better growth. Overall, the budikdamber system maintained stable water quality and supported satisfactory fish performance when stocking density was managed appropriately.